P141 Persistent bacterial bronchitis in adults – a precursor to bronchiectasis?. (12th November 2019) - Finch, S; Carreto, L; Abo-Leyah, H; Browne, A; Fardon, TC; Chalmers, JD
Abstract : Introduction: Bronchiectasis is both a radiological diagnosis and a clinical syndrome. In children, a pre-bronchiectasis condition called persistent bacterial bronchitis (PBB) has been described, but this is not recognised in adults. Here we describe a series of adult patients with clinical features of bronchiectasis without radiological bronchial dilation. Methods: CT scans from patients with clinically suspected bronchiectasis referred to a Bronchiectasis clinic between 2011 and 2017 were reviewed by two blinded observers, maximal Bronchio-arterial ratio was recorded. Fleischner society guidelines were used to diagnose radiological bronchiectasis. Adult PBB was defined by chronic or recurrent productive cough, laboratory evidence of bacterial infection in sputum cultures, responsiveness of cough to antibiotic treatment and exclusion of alternative causes of cough (asthma, COPD, smoking) without radiological evidence of Bronchiectasis. Results: 90 patients met the criteria for adult PBB, 56.7% female, mean age 67. 63 (70%) had positive sputum cultures at presentation. Of those with recurrent positive sputum samples, 68.9% had persistent Haemophilus influenzae infection. Pseudomonas aeruginosa was isolated in 7 patients. Applying the bronchiectasis severity index (BSI), the mean score was 7, indicating a significant burden of disease despite no radiological abnormality. 55 patients were treated with long term antibiotics, typically long term azithromycin. 42 had a documented reduction in exacerbation frequency and/or symptoms. 35 patients had follow-up CT scans of which 10 (28.6%) patients developed overt radiological bronchiectasis. Conclusion: Adult PBB is a distinct disease entity representing a precursor to overt bronchiectasis in a significant number of patients. The condition is clinically similar to Bronchiectasis and responds to long term antibiotics. Further work to clearly define the condition and its natural progression is required.